2021
DOI: 10.1080/1369118x.2021.1962942
|View full text |Cite
|
Sign up to set email alerts
|

Insta(nt)famous? Visual self-presentation and the use of masculine and feminine issues by female politicians on Instagram

Abstract: This study examines how female politicians are using Instagram to present themselves to the electorate and how this affects audience engagement. A manual content analysis was conducted to explore how female politicians, compared to male politicians (N = 40), use Instagram in terms of visual self-presentation, the use of masculine and feminine issues, and how this may lead to increased engagement (i.e., likes and comments). In total, N = 762 posts were manually analyzed. The study shows that female politicians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 56 publications
2
18
0
1
Order By: Relevance
“…Facebook represents a unique social network in this regard in that it allows to convey information through two different types of profile: One is strictly personal whereas the other is public and can reasonably reflect the interaction between the politician and the staff members in order to effectively shape the political campaign. As for the public profiles, results from both studies indicated that there was no effect of gender on facial prominence, confirming the findings obtained by Jungblut and Haim (2021) in relation to European Elections (see also Brands et al, 2021 ). Hence, there was no evidence of any gender-based discrepancy in the way male and female politicians visually present themselves.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Facebook represents a unique social network in this regard in that it allows to convey information through two different types of profile: One is strictly personal whereas the other is public and can reasonably reflect the interaction between the politician and the staff members in order to effectively shape the political campaign. As for the public profiles, results from both studies indicated that there was no effect of gender on facial prominence, confirming the findings obtained by Jungblut and Haim (2021) in relation to European Elections (see also Brands et al, 2021 ). Hence, there was no evidence of any gender-based discrepancy in the way male and female politicians visually present themselves.…”
Section: Discussionsupporting
confidence: 80%
“…Although several studies have been dealing with the face-ism effect in social media, to the best of our knowledge, no previous study has analyzed politicians’ social media profiles as a function of whether the profile is personal in nature, or it is related to the public activity of the person as a politician. Overall, in line with Brands et al (2021) and Jungblut and Haim (2021) , we expected to observe no higher facial dominance of male as compared to female candidates. More specifically, although we had no a priori hypotheses, we also explored whether face-ism in the more informal private profiles.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…A comparison of self-and media-presentation of female and male candidates during the 2019 European Election on social media and in the news showed that "female candidates are actually portrayed more often happy on SNS [social networking sites] than in the news, which echoes the interpretation of a visual communication strategy that is in line with the strategic stereotype theory" (Haim and Jungblut, 2020, p. 15). Examination of visual self-presentation of Dutch and American politicians on Instagram led to a result that visual depiction did not differ by gender, except in the case of clothing: female politicians appeared more often in casual clothing (Brands et al, 2021). In a study by Carlson and Håkansson (2022), visual party communication on Facebook in the 2019 EU election campaigns' national level showed that the depiction of smiling faces and casual clothing was more frequent among female than male politicians.…”
mentioning
confidence: 98%